Enhancing Audit Quality: Insights from Market Dominance, Partner Rotation and Audit Firm Tenure - Etty Murwaningsari; Tjiendradjaja Yamin; Muhammad Nuryanto Amin; Anne Lorraine A. Casapao (The Indonesian Journal of Accounting Research, 2026)
We explore the impact of audit market dominance, partner rotation, and audit firm tenure on audit quality, utilizing data from 534 entities listed on the Indonesian Stock Market between 2018 and 2022, resulting in 2.670 entity-year observations. Our study introduces a novel measure of audit market dominance by utilizing market capitalization as a replacement for traditional market share measurements. The outcomes highlight that audit market dominance and partner rotation favour audit quality, while audit firm tenure weakens these effects. These results emphasize the importance of mandatory rotation policies to uphold auditor independence and objectivity, particularly in concentrated audit markets. Our study remains robust under various alternative tests. Policymakers should enforce stricter regulations on the tenure of auditing firms and promote obligatory audit firm rotation to enhance audit quality. Encouraging smaller audit firms to join global networks may also elevate industry-wide standards. Investors are advised to be cautious about entities audited by firms with extended tenures and prioritize those with frequent audit partner rotations. This study is limited to entities in Indonesia and relies on its assessment of audit quality, employing going concern as a proxy. Subsequent studies may broaden the geographical scope and incorporate additional audit quality metrics to enhance the generalizability and robustness of the results.